Frontispiece: Metal Complexes of Singly, Doubly and Triply Linked Porphyrins and Corroles: An Insight into the Physicochemical Properties. Issue 24 (27th April 2022) - Hazari, Arijit Singha; Chandra, Shubhadeep; Kar, Sanjib; Sarkar, Biprajit
Abstract : Metal complexes of doubly and triply linked porphyrins and corroles are presented with a particular focus on their electrochemical, electronic and magnetic properties. The potential utility of these compounds as electrocatalysts for energy related research is elucidated with the help of recent examples.